PELAKSANAAN AKAD QARDH WA AL-IJARAH PADA PRODUK DANA TALANGAN PENDIDIKAN DI KOPERASI MITRA DHUAFA CABANG KADUGORA - Selly Sri Wulandari; Neni Nuraeni; Mila Badriyah (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2020)
The education bailout product (DTP) is a solution for members who have difficulty paying fees to complete their children's education. This study aims to determine how the implementation of the qardh wa al-ijarah contract on the DTP product and to know the review of Sharia Economic Law on the implementation of DTP. The method used is descriptive that is to explain how the implementation of the qardh wa al-ijarah contract on the DTP product. Based on the results of the study it was concluded that the implementation of the qardh wa al-ijarah contract on the DTP product used the qardh wa al-ijarah agreement, where the qardh contract was a KOMIDA & members' debt and agreement agreement, while the ijarah contract was a KOMIDA agreement and members where members were willing to pay for educational services. According to the review of Sharia Economic Law in DSN MUI Fatwa No.29 of 2002 as a reference for the implementation procedure of DTP products and the muqalah fiqh principle is contradictory because the benefits of the Ujrah given are based on the bailout funds provided, so that the law is riba and does not meet Islamic economic values as basic principles muamalah.